Central Diabetes Insipidus in a Young Feline - Strack, Adriane; Moretto, Luana; Di Concilio, Carla; Pereira, Marcy Lancia (Acta Scientiae Veterinariae, 2020)
Background: Central diabetes insipidus (CDI) is an endocrine disorder caused by the failure to produce, transport, or release ADH. This disease may show a primary etiology (idiopathic or congenital) or a secondary one (trauma or neoplasms). It is characterized by signs such as polyuria and polydipsia. The definitive diagnosis is obtained by the two-step water deprivation test; the absence of adequate urinary concentration in the first stage confirms the diagnosis of diabetes insipidus and, in the second stage, the response to the application of synthetic desmopressin confirms a central origin. Because CDI is rare in felines, the aim of this study was to report the occurrence of a case of CDI, probably of congenital primary origin, in an 8-month-old kitten. Case: An 8-month-old male feline, castrated, 3.2 kg, was brought to consultation with a report of polydipsia, polyuria, smaller size and weight, and lower activity when compared to his brother, for several months. On physical examination, lethargy, body score 2/5, and mild dehydration were noted, as well as deciduous teeth that should have already been replaced. Abdominal ultrasound and laboratory tests were requested, which ruled out chronic kidney disease (CKD), diabetes mellitus (DM), hyperadrenocorticism (HAC), and hyperthyroidism. Due to the fact that urinalysis evidenced hyposthenuria (urinary density [UD] 1.004), CDI was suspected. The patient underwent a water deprivation test and, after 7.5 h, lost 4.7% of his initial weight, while UD was 1.012, confirming the diagnosis of DI. The investigation then proceeded to the evaluation of the response to synthetic desmopressin by the application of 5 U IM. Two h later, UD was 1.019, confirming the diagnosis of CDI. The prescribed treatment was oral desmopressin at a dose of 100 μg BID. Upon return after 30 days, the feline had gained weight, was well hydrated, and the tutor reported higher activity. A new urinalysis showed a UD of 1.004 and inactive sediment. The tutor was asked to start administering the drug three times a day. However, noting that the patient’s quality of life had significantly improved, and wishing to spare the animal from the stress of taking medication once more a day, she chose not to modify the therapy and not to perform additional tests, due to financial limitation. Discussion: First, CKD, DM, HAC, and hyperthyroidism, more common conditions, were ruled out, and the investigation then proceeded to a water deprivation test. The feline lost 3% to 5% of the initial weight and UD was on the borderline between hypo- and isosthenuria, as described in the literature for the diagnosis of DI. In the second stage of the test, slight urinary concentration was observed after the application of synthetic desmopressin, which confirmed the diagnosis of CDI. The dose of desmopressin prescribed for home treatment, 100 μg BID, was effective to relieve the clinical signs, but urine remained in hyposthenuria in the interval between administrations, suggesting that, for this patient, treatment would be more effective by administering the medication three times a day, in order to maintain an adequate serum concentration. Due to the diagnosis of CDI and the feline being young, the condition’s primary origin is believed to be congenital. It is also suspected that the patient may still have congenital hypothyroidism, due to the clinical signs of late tooth exchange and constant lethargy, in addition to laboratory results of thyroid hormones below reference levels. However, because thyroid tests were made by chemiluminescence, a repetition by radioimmunoassay is indicated. If hypothyroidism is confirmed, it would be possible to assume a common etiological factor between CDI and hypothyroidism, such as hypothalamicpituitary malformation.